Perempuan Dalam Revivalisme (Gerakan Revivalisme Islam dan Politik Anti Feminisme di Indonesia) - Zuhdi, M Nurdin (Sunan Kalijaga State Islamic University & The Asia Foundation, 2010)
Conversations about women will never cease to be discussed. Because of concerns about women's studies has always been an issue that attracts attention. But unfortunately, the conversation about women in Islam has always rested on the conclusion that Islam is less or even no female friendly. It has been proven in every blade of which is recorded by history in which the marginalization of women is still happening everywhere and in almost all fields, both in the workplace, in households, communities, cultures and even countries. Marginalization of women does not only occur in Islam alone, even going in the other major religions such as Christianity, Catholicism, Hinduism and Buddhism. And in conversation, every woman always on the contested positions, especially in the discourse of the Islamic revival movement that will be discussed in this article. Movement of Islamic revivalism has thought that leads to return to the teachings of religion. However, in the context of women who claimed to be returning to the teachings of religion is a house of women, ie. women returning to domestication. Here, the struggle against the rise of the women's movement into thinking clashed with the Islamic revival. This article tried to explain the thoughts and ideas of the Islamic revival movement and their implications for the progress and the rise of women in Indonesia.